2018
DOI: 10.1371/journal.pone.0201182
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidogenic cross-seeding of Tau protein: Transient emergence of structural variants of fibrils

Abstract: Amyloid aggregates of Tau protein have been implicated in etiology of many neurodegenerative disorders including Alzheimer's disease (AD). When amyloid growth is induced by seeding with preformed fibrils assembled from the same protein, structural characteristics of the seed are usually imprinted in daughter generations of fibrils. This so-called conformational memory effect may be compromised when the seeding involves proteins with non-identical sequences leading to the emergence of distinct structural varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 71 publications
(70 reference statements)
3
28
0
Order By: Relevance
“…The addition of pre-formed aggregate seeds furthermore resulted in an aggregation kinetics with a very short lag time (Fig. 2B), in agreement with previous studies on seeded tau aggregation (27). This suggests that small amounts of aggregates formed by the tau 168-368 fragment may cause full-length tau to form fibrils, even though the protein is normally much more conformationally stable and remains soluble.…”
Section: Resultssupporting
confidence: 92%
“…The addition of pre-formed aggregate seeds furthermore resulted in an aggregation kinetics with a very short lag time (Fig. 2B), in agreement with previous studies on seeded tau aggregation (27). This suggests that small amounts of aggregates formed by the tau 168-368 fragment may cause full-length tau to form fibrils, even though the protein is normally much more conformationally stable and remains soluble.…”
Section: Resultssupporting
confidence: 92%
“…A recent study reported that cross-seeding of tau protein lead to the emergence of structural variant of fibrils [61], again supporting the possibility that the difference in size we observed may be attributed to the mutated tau fragment tagged with eGFP. To explore this possibility, we have conducted cell-free conversion assay in which full-length recombinant tau was used as substrate.…”
Section: Prionsupporting
confidence: 86%
“…This question is essential in the context of prion-like mechanisms (Sanders et al, 2014;Woerman et al, 2016), where one needs to understand the conditions required to ensure the faithful propagation of a given strain. Although cellular work has suggested that strain properties (based on proteolysis patterns and cellular localization of aggregates) can be maintained through seeding (Kaufman et al, 2016), other in vitro work suggested that properties of the seeded protein, and not the seed, dictate the structure of the obtained aggregates (Nizynski et al, 2018). Fichou and coworkers (Fichou et al, 2018a) showed that cofactor-assisted seeding achieve a mild degree of structural convergence compared to heterogeneous heparin fibrils, but without deciphering its origin.…”
Section: Discussionmentioning
confidence: 99%